Experiential Learning: Empowering Students to Take Control of Their Learning by Engaging Them in an Interactive Course Simulation Environment. (5th May 2015) - Marin, Elena
Abstract: Engaging students in an interactive course simulation and giving them the responsibility to design and implement a lesson plan can be viewed as a way to empower students to take control of their own learning process. The aim of this paper is to present the results of a study in which second year students from the Educational Science department were engaged in an interactive lecture, which consisted of designing and implementing a teaching activity. All in all, we want to bring into discussion the importance of creating, among students, a sense of ownership over their own learning.